Digital Islamic Studies Learning Methodology for Generation Z - Humaida; Intan Kurnia Wati; Mukmin (Program S3 Pendidikan Islam Institut Pesantren KH. Abdul Chalim Pacet Mojokerto, 2025)
This study aims to explore the conceptual foundations, methodological orientations, and practical strategies necessary for designing Islamic studies that are relevant to Generation Z. As digital natives, Generation Z develops cognitively, socially, and religiously within an environment dominated by rapid technological advancement, visual communication, and continuous connectivity. This condition creates an urgent need to formulate a methodological framework for Digital Islamic Studies that aligns with their learning patterns and digital behavior. Using a library research design with a content analysis approach, the study examines key academic sources and previous research related to digital literacy, Islamic education, and online religious engagement. The findings indicate that digital platforms such as TikTok, Instagram, and YouTube have become major epistemic spaces for Gen Z, reshaping religious authority, learning preferences, and modes of value internalization. The study also identifies significant challenges, such as misinformation, limited educator competence, and the lack of structured digital literacy frameworks, that hinder effective implementation of digital Islamic learning. The research concludes that a comprehensive, adaptive, and interdisciplinary methodology is essential for ensuring that Islamic knowledge remains accurate, meaningful, and contextually relevant in the digital age, while also recommending further empirical studies to validate and refine the proposed methodological model.